Multiwell plates for complementation tests of Fusarium. - C. J. R. Klittich; J. F. Leslie (Fungal Genetics Reports, 1988)
Vegetative compatibility group (VCG) is a phenotype used to subdivide and categorize populations of Fusarium species (Correll et al. 1987 Phytopathology 77:1640-1646).